TAIGA experiment: present status and perspectives - Budnev, N.; Astapov, I.; Gress, T.; Grinyuk, A.; Grishin, O.; Dyachok, A.; Fedorov, O.; Haungs, A.; Horns, D.; Huege, T.; Ivanova, A.; Kalmykov, N.; et al. (Journal of Instrumentation, 2017)
The TAIGA observatory addresses ground-based gamma-ray astronomy at energies from a few TeV to several PeV, as well as cosmic ray physics from 100 TeV to several EeV . TAIGA will be located in the Tunka valley, ~ 50 km West from Lake Baikal. The different detectors of the TAIGA will be grouped in 6 arrays to measure Cherenkov and radio emission as well as electron and muon components of atmospheric showers. The combination of the wide angle Cherenkov detectors of the TAIGA-HiSCORE array and the 4-m Imaging Atmospheric Cherenkov Telescopes of the TAIGA-IACT array with their FoV of 10×10 degrees and underground muon detectors offers a very cost effective way to construct a 5 km$^2$ array for gamma-ray astronomy.